2012
DOI: 10.1590/s1516-35982012000900013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional reduction of protein and usage of enzyme in the diet of light layers

Abstract: -The objective of this study was to evaluate the reduction of protein, the formulation of diets and supplementation of an enzyme complex for laying hens. The layers were distributed in a completely randomized 2 × 2 × 2 factorial arrangement, with two levels of crude protein reduction (0.0 and 4.0 g/kg), two kinds of diet formulation (without and with reformulation, considering 75 kcal of metabolizable energy) and two enzyme supplementations (without and with enzyme complex supplementation), totalizing 8 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Several commercial guidelines for laying hens (Brown, 2011 andLohman, 2010) for crude protein (CP) levels varies from 17.4% to 18.2% (19.1 20.0 g of CP/d) per hen. Which were higher than the recommendation of many recent reports (Bonilla et al, 2012;Lima et al, 2012 andRamarao et al, 2011). Higher levels of protein/ amino acids in diet will increase nitrogen excretion, ammonia emission, and taxing the ecosystem by contaminating surface water bodies (Latshaw and Zhao, 2011) also often result in higher feed cost.…”
Section: Introductionmentioning
confidence: 51%
“…Several commercial guidelines for laying hens (Brown, 2011 andLohman, 2010) for crude protein (CP) levels varies from 17.4% to 18.2% (19.1 20.0 g of CP/d) per hen. Which were higher than the recommendation of many recent reports (Bonilla et al, 2012;Lima et al, 2012 andRamarao et al, 2011). Higher levels of protein/ amino acids in diet will increase nitrogen excretion, ammonia emission, and taxing the ecosystem by contaminating surface water bodies (Latshaw and Zhao, 2011) also often result in higher feed cost.…”
Section: Introductionmentioning
confidence: 51%
“…Regarding egg mass, it was found that this variable was influenced by diets with nutritional reduction. However, Lima et al (2012) did not observe any significant treatment effect on the egg mass when providing diets with low levels of crude protein (0.0 and 4.0 g/kg) with or without supplementation of enzymatic complex for light laying hens at 30 weeks old. Similar results were also found by Vieira et al (2016), who did not observe any significant differences in egg production of light laying hens at peak production fed diets with reduced energy, proteins, and amino acids, with or without the inclusion of proteases (Streptomyces fradiae, 0.125 g kg −1 in the diet and Bacillus licheniformis, 0.250 g kg −1 in the diet) in their composition.…”
Section: Discussionmentioning
confidence: 70%
“…Several commercial guidelines for laying hens [ 1 , 2 ] were recommended for crude protein (CP) levels, which vary from 17.4% to 18.2% (19.1-20.0 g of CP/d) per hen. Which appeared to higher than the recommendation of many recent reports [ 3 - 6 ] higher levels of protein/amino acids in diet will increase nitrogen excretion, ammonia emission, and taxing the ecosystem by contaminating surface water bodies [ 7 ] also often result in higher feed cost. Blair et al ,[ 8 ] obtained optimum layer performance when they were fed on low-protein diet (13.5%), which was properly supplemented with essential amino acids compared to layers fed 17% CP diet.…”
Section: Introductionmentioning
confidence: 79%